Answer:
If
then
.
If
then
.
Step-by-step explanation:
In order to write the polynomial as the product of linear factors, we need to find the roots of the polynomial. A quadratic equation is defined as:
![ax^2+bx+c](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc)
Because the given polynomial expression is a quadratic equation, we can use the following equations for calculating the roots:
![x1=(-b/2a)+\sqrt{b^2-4ac}/2a](https://tex.z-dn.net/?f=x1%3D%28-b%2F2a%29%2B%5Csqrt%7Bb%5E2-4ac%7D%2F2a)
![x1=(-b/2a)-\sqrt{b^2-4ac}/2a](https://tex.z-dn.net/?f=x1%3D%28-b%2F2a%29-%5Csqrt%7Bb%5E2-4ac%7D%2F2a)
Since the second term sign is not given, then we can write the expression as:
, in which a=1, b=s2 where 's' represents a sign (- or +), and c=10.
Using the equation for finding the roots we obtain:
![x1=(-sb/2a)+\sqrt{b^2-4ac}/2a](https://tex.z-dn.net/?f=x1%3D%28-sb%2F2a%29%2B%5Csqrt%7Bb%5E2-4ac%7D%2F2a)
; notice that ![(sb)^{2} = 2^{2}](https://tex.z-dn.net/?f=%28sb%29%5E%7B2%7D%20%3D%202%5E%7B2%7D)
![x1=(-s1)+\sqrt{-36}/2](https://tex.z-dn.net/?f=x1%3D%28-s1%29%2B%5Csqrt%7B-36%7D%2F2)
![x1=-(s1)+6i/2](https://tex.z-dn.net/?f=x1%3D-%28s1%29%2B6i%2F2)
![x1=-(s1)+3i](https://tex.z-dn.net/?f=x1%3D-%28s1%29%2B3i)
![x2=(-sb/2a)-\sqrt{b^2-4ac}/2a](https://tex.z-dn.net/?f=x2%3D%28-sb%2F2a%29-%5Csqrt%7Bb%5E2-4ac%7D%2F2a)
; notice that (s2)²=2^2
![x2=(-s1)-\sqrt{-36}/2](https://tex.z-dn.net/?f=x2%3D%28-s1%29-%5Csqrt%7B-36%7D%2F2)
![x2=-(s1)-6i/2](https://tex.z-dn.net/?f=x2%3D-%28s1%29-6i%2F2)
![x2=-(s1)-3i](https://tex.z-dn.net/?f=x2%3D-%28s1%29-3i)
If we consider 's' as possitive (+) the roots are:
and ![x2=-1-3i](https://tex.z-dn.net/?f=x2%3D-1-3i)
Whereas if we consider 's' as negative (-) the roots are:
and ![x2=1-3i](https://tex.z-dn.net/?f=x2%3D1-3i)
The above means that if the equation is
, then we can express the polynomial as:
.
But, if the equation is
, then we can express the polynomial as:
.